The correlation between systemic immune-inflammation index and major depression in patients with depression - Yixuan Bai; Zanxi Fang; Huirong Dai; Qiao Zhang; Pan You (Frontiers in Psychiatry)
AimsTo explore the relationship between the systemic immune-inflammation index (SII) and the severity of depression.MethodsThis retrospective study included 750 patients who were hospitalized at Xiamen Xianyue Hospital and diagnosed with depression from January 2022 to December 2023. The SII was defined as the platelet count × neutrophil count/lymphocyte count. The participants were divided into a mild to moderate depression group (299 patients) and a major depression group (451 patients). Univariate and multivariate Logistic regression analysis, subgroup analysis, sensitivity analysis, and receiver operating characteristic (ROC) curve analysis were used to explore the correlation between the SII and the severity of depression.ResultsAccording to the multivariate Logistic regression analysis, the SII was independently associated with the risk of major depression (P < 0.05). For every 1- unit and 1-standard-deviation increase in the SII, the risk of major depression increased by 0.1% and 25.3%, respectively (OR: 1.001, 95% CI: 1.000–1.001, P = 0.008; OR: 1.253, 95% CI: 1.061–1.480, P = 0.008), and each 1-unit increase in the Log10SII was associated with a 124.8% increased risk of major depression (OR: 2.248, 95% CI: 1.231–4.106, P = 0.008). Subgroup analysis and sensitivity analysis revealed significant associations between the SII and the risk of major depression was significant in multiple specific populations (P < 0.05). ROC curve analysis revealed that the area under the curve (AUC) value for using the SII to predict the risk of major depression was 0.585 (95% CI: 0.507–0.591, P = 0.024).ConclusionHigher SII values are strongly associated with a greater risk of major depression.